Od dveh generalov do dveh storitev - Prtenjak, Matjaž (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
In the world of artificial intelligence, we quickly fall into the trap of developing overly complex systems because of its help. In this spirit and the spirit of the Internet and unlimited possibilities, we also seize the idea of ​​microservices. We divide the system into smaller services that generally own their own data, and the communication between them takes place via the network, remote calls or messages. The solution looks good, natural and everyone recommends it, but they keep the complexity quiet. We replace the function call in a dynamic library with communication over an unreliable network. We replace the local transaction with a distributed one, and the simple order of execution with events that can come multiple times, never, or even in the completely wrong order. It turns out that microservices are not a technical solution, but an organizational solution for large enough organizations.